2015 update on the diagnosis and management of neoplastic pericardial disease. (April 2015) - Lestuzzi, Chiara; Berretta, Massimiliano; Tomkowski, Witold
Abstract : The best approach in diagnosis and treatment of neoplastic pericardial disease has not been defined yet. The authors report the most recent literature about the new diagnostic techniques that are useful to improve the diagnosis. The literature about the therapeutic options is critically reviewed, in order to give suggestions of use to the clinical practice. Pericardial effusion may require urgent drainage; the solid component, however, becomes predominant in some cases. Neoplastic pericardial disease should be assessed following oncologic criteria evaluation of the neoplastic burden; outcome classified as complete or partial response, stable or progressive disease and – in cases with progression – event-free survival. Systemic chemotherapy may be effective in lymphomas and possibly in breast carcinomas. Intrapericardial chemotherapy with systemic chemotherapy is the treatment of choice in lung cancer. Pericardial window with systemic chemotherapy is also effective in preventing the accumulation of large amount of fluid.